Telaah Teoretis tentang Ilmu Qiraat dalam kajian Al-Qur’an - Rahmana, Afrida Ulya Rahmana Ulya (Maliki Interdisciplinary Journal, 2025)
Qira 'at is a discipline that deals with variations of reading the qur 'an as it is passed down to the messenger of god. And it's inherited through a valid sanad. The appearance of qira 'at is based on the concept of sab 'atu ahruf, which is given as a convenient way for people with differing dialects and reading skills. In the days of the spread of Islam, scholars have established qira 'at's historical criteria to match the Assyrian rasm, the Arabic code, and the valid sanads to maintain the integrity of qur 'an. Based on these criteria, qira 'at is classified into several stages, such as mutawattir,, ahad, shaz, maudhu ', and mudraj, where only qira 'at sahih may be allowed to exist. The study shows that learning qira 'at has great urgency, not only in the original preservation of the qur 'an, but also in deepening of meaning, deepening of tajwid science, understanding of Arabic, and enambling of spiritual experience. Thus, the qira 'at science is a fundamental aspect of maintaining the purity of qur 'an and reinforcement a Muslim's relationship with divine revelation.